2010
DOI: 10.5539/ijb.v2n2p126
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Aframomum Melegueta (Alligator Pepper)

Abstract: Antibacterial activity of Aframomum melegueta was tested on salmonella spp, Escherichia coli, Shigella spp and klebsiella spp. Ethanol and distilled water were used as solvents for the extraction of the plant. The ethanolic extract was found to be most effective at high concentration of 50mg/ml on all the isolates. The zones of inhibition of klebsiella spp, salmonella spp, E. coli and Shigella spp are 30mm,15mm,20mm,and 15mm respectively with ethanolic extract. The aqueous extract was found to be less effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 4 publications
4
53
0
Order By: Relevance
“…The plant was found to contain steroids, saponins and tannins which could explain the activities observed [18,21]. Antimicrobial activity of the bark extract of this plant, using the microdilution method, presented better results than well diffusion method.…”
Section: Cussonia Arborea (Ca) Dissotis Longipetala (Dl Lonchocarpusmentioning
confidence: 99%
See 4 more Smart Citations
“…The plant was found to contain steroids, saponins and tannins which could explain the activities observed [18,21]. Antimicrobial activity of the bark extract of this plant, using the microdilution method, presented better results than well diffusion method.…”
Section: Cussonia Arborea (Ca) Dissotis Longipetala (Dl Lonchocarpusmentioning
confidence: 99%
“…It was moderately active on C. krusei, P. stuartii, P. vulgaris and E. coli, (MIC ≤8mg/ml); and less active on P. aeruginosa, and E. coli JM109 The phytochemical screening of this plant showed that it contains tannins, alkaloids and saponins, hence the antimicrobial properties demonstrated by this plant could be attributed to some of these biological active components [17][18]. This plant was reported to have very important antioxidant and reducing power [23] but the antimicrobial properties of the plants are reported here for the first time.…”
Section: Cussonia Arborea (Ca) Dissotis Longipetala (Dl Lonchocarpusmentioning
confidence: 99%
See 3 more Smart Citations